A Bibliometric Analysis of Quality Research Papers in Islamic Education: Evidence from Scopus - Machali, Imam; Suhendro, Eko (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to reveal bibliometric data related to the study of Islamic education. Design/methods/approach – This study uses a bibliometric analysis method to examine publishing trends and emerging themes surrounding the study of Islamic education. The study is limited to the types of documents, articles, proceedings, reviews, and book chapters. This study uses the Scopus database, and the data was collected on July 1, 2021. The targeted data was retrieved by applying the search keywords: “Islamic Education” OR “Madrasah” OR “Islamic School.” Findings – The results of this study reveal that there has been an increase in the study of Islamic Education in Scopus-indexed journals over the last five years, with most of them written by Indonesian scientists. However, most articles published in the two journals are not specific to the study of Islamic education or religious studies. Research implications/limitations – This study is limited to Islamic education research in the Scopus database. This study only looks at bibliometric data analysis. Further studies based on the systematic literature review method can investigate the findings. Islamic education researchers can use the results of this study to develop future research topics. Practical implications – This study sheds light on the evolution of Islamic education research. The results of this study have implications for a more focused direction of Islamic education research through information science tools.